Gain enhancement for patch antenna loading with slotted parasite antenna based on metasurface super substrate - Bashar B.S.; Rhazali Z.A.; Misran H.; Ismail M.M.; Al-Sharify M.T. (American Institute of Physics Inc., 2024)
In modern wireless systems, the microstrip patch antenna has attracted considerable attention due to its low-profile structure, compact size, easy production, and low value. The narrow operating bandwidth has an intrinsic disadvantage. It was suggested to improve the antenna bandwidth and gain, the performance and operating mechanism of the antenna proposed, on a thinner substrate metamaterial (MTS) antenna. The antenna was designed with a supersubstrate with relative allowability of 4.0, a thickness of 1.5 mm, and coaxial feeding technology to show its concept. Simulations were carried out using the design tool CST. The proposed antenna was supplied under the metasurface with an aperture-connected layer. The antenna's design enables to work with resonant frequencies to increase bandwidth and gain. A genetic algorithm was used to optimize the geometrical parameters of that antenna to achieve the best gain performance. This structure, together with the patch of the antenna configuration, achieves a reflecting S11 coefficient less than -48db, with a gain =6.1 db. 2023 Author(s).